Psychometric properties of the HEXACO personality inventory A field study on a sample of university of Mohammed Boudiaf -Msila- students - GUERRA, Noureddine; BRAKHLIA, Abdelghani (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The aim of this research is to investigate the psychometric properties of the HEXACO personality inventory in the Algerian language, and to examine its underlying factors. A principal component analysis with orthogonal rotation was applied and the factors were rotated to a varimax solution, on a sample of 733 participants in the University of Mohamed Boudiaf -M'Sila, From different educational levels. A descriptive method was used to realize the objectives of the study, using the HEXACO personality inventory -60 items to measure the six dimensions of personality. The psychometric properties of the HEXACO-PI -60 were examined and found to be satisfactory. Regarding the difference between males and females on personality dimensions, the results indicated that females averaged higher than men on Emotionality factor and relatively higher on the other factors, these findings are consistent with the theoretical explanation in the HEXACO model of personality. Moreover, results from principal component analysis confirmed six factors in the Algerian sample. These findings confirm that HEXACO-60 personality inventory is reliable and valid measure of the six personality dimensions, these results are consistent with the findings in the original English version of the HEXACO-60 personality inventory.